COVID-19 vaccination: engagement behavior patterns and implications for public health service communication. Issue 2 (22nd February 2022) - Azer, Jaylan; Alexander, Matthew
Abstract : Purpose: COVID-19 vaccinations face a backdrop of widespread mistrust in their safety and effectiveness, specifically via social media platforms which constitute major barriers for the public health sector to manage COVID-19 (and future) pandemics. This study provides a more nuanced understanding of the public's engagement behavior toward COVID-19 vaccinations. Design/methodology/approach: Using Netnography, this study explores the public's interactions with vaccine communications by the WHO via Facebook. From WHO posts about the COVID-19 vaccination 23, 726 public comments on Facebook were extracted and analyzed. Findings: Building on crisis communication, health and engagement literature, this paper identifies and conceptualizes seven patterns of engagement behavior toward the COVID-19 vaccination and develops the first framework of relationships between these patterns and the extant vaccine attitudes: vaccine acceptance, hesitancy and refusal. Practical implications: This paper helps policymakers identify and adapt interventions that increase vaccine confidence and tailor public health services communications accordingly. Originality/value: This research offers the first typology of patterns of engagement behavior toward COVID-19 vaccinations and develops a framework of relationships between these patterns and the existing understanding in health literature. Finally, the study provides data-driven communication recommendations to public health service organizations.